2006
DOI: 10.1007/s00161-005-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic damage mechanics for viscoelastic ice

Abstract: We present a formulation of continuum damage in glacier ice that incorporates the induced anisotropy of the damage effects but restricts these formally to orthotropy. Damage is modeled by a symmetric second rank tensor that structurally plays the role of an internal variable. It may be interpreted as a texture measure that quantifies the effective specific areas over which internal stresses can be transmitted. The evolution equation for the damage tensor is motivated in the reference configuration and pushed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Pralong and Funk, 2005;Duddu and Waisman, 2012) as well as cohesive snow (Borstad and McClung, 2011). Pralong et al (2006) demonstrated that this equivalence scheme is thermodynamically consistent for damage as well as healing (damage reversal) of ice. We adopt this equivalence scheme here, which leads to the following definition of an effective stress,…”
Section: Linear Mapping Between Physical and Effective Spacesmentioning
confidence: 82%
“…Pralong and Funk, 2005;Duddu and Waisman, 2012) as well as cohesive snow (Borstad and McClung, 2011). Pralong et al (2006) demonstrated that this equivalence scheme is thermodynamically consistent for damage as well as healing (damage reversal) of ice. We adopt this equivalence scheme here, which leads to the following definition of an effective stress,…”
Section: Linear Mapping Between Physical and Effective Spacesmentioning
confidence: 82%
“…A novel suggestion to model calving may be given by damage mechanics (Pralong et al 2003(Pralong et al , 2006Pralong and Funk 2005), which may be included into full Stokes flow models. Damage denotes a continuous field that is defined by source and sink terms related to the stress field, as formulated by Pralong and Funk (2005):…”
Section: Grounded Icementioning
confidence: 99%
“…Different physical processes were put forward to explain this behavior: Several attempts have been made to link log‐periodic oscillations to a system that contains a relaxation mechanism reducing the damage [ Ide and Sornette , ]. However, the existence of such a relaxation mechanism in ice (negative feedback such as healing) is rather uncertain at such small time scales. The evolution of damage anisotropy in the case of a shearing fracture was proposed by Pralong [] and Pralong et al [] as a possible explanation for such an oscillating behavior. The existence of log‐periodic oscillations emerges naturally from the classic constitutive equations of anisotropic damage evolution and ice deformation in the case of shearing flow. The appearance of the log‐periodic oscillations could also result from dynamic crack interaction, as shown by Huang et al [] and Sahimi and Arbabi [].…”
Section: Instabilities Of Cold Glaciersmentioning
confidence: 99%